Rasch-Built Measure of Pleasant Touch through Active Fingertip Exploration - Klöcker, Anne; Penta, Massimo; Arnould, Carlyne; Thonnard, Jean-Louis (Frontiers in Neurorobotics, 2012)
Background: Evidence suggests that somatic sensation has a modality for pleasant touch. Objective: To investigate pleasant touch at the fingertip level (i.e., glabrous skin site) through the elaboration of a linear unidimensional scale that measures (i) various materials according to the level of pleasantness they elicit through active fingertip explorations and (ii) subjects according to their pleasantness leniency levels. Subjects: We enrolled 198 healthy subjects without any neurological disease. Methods: Blindfolded subjects actively explored 48 materials with their index fingertips and reported the perceived pleasantness of each on a 4-level scale. The fingertip moisture levels on each subject were measured before the experimental session. Data were analyzed using the Rasch model. Results: We elaborated unidimensional linear scale that included 37 materials according to their pleasantness of touch. The pleasantness level of 21 materials was perceived differently, depending on the fingertip moisture levels of the subjects. Conclusion: Based on our findings, we formulated a Pleasant Touch Scale. Fingertip moisture levels appeared to be a major factor for (un)pleasant feelings during active exploration.